Arthroscopic Findings of the Joint Distraction for the Patient With Chondrolysis of the Ankle. Issue 2 (1997) - Kanbe, Katsuaki; Hasegawa, Atsushi; Takagishi, Kenji; Kaneko, Hiroyuki; Nakajima, Yasuyuki
Abstract : This case report describes arthroscopic findings of the effect on articular distraction of ankle joint by means of external fixator for the patient with chondrolysis. Arthroscopy showed fibrocartilage tissue lying between the talus and tibia to protect damaged articular surfaces although apparent repair of surface cartilage failed to find.